Social isolation during COVID‐19 lockdown impairs cognitive function. Issue 4 (24th March 2021) - Ingram, Joanne; Hand, Christopher J.; Maciejewski, Greg
Summary: Studies examining the effect of social isolation on cognitive function typically involve older adults and/or specialist groups (e.g., expeditions). We considered the effects of COVID‐19‐induced social isolation on cognitive function within a representative sample of the general population. We additionally considered how participants 'shielding' due to underlying health complications, or living alone, performed. We predicted that performance would be poorest under strictest, most‐isolating conditions. At five timepoints over 13 weeks, participants ( N = 342; aged 18–72 years) completed online tasks measuring attention, memory, decision‐making, time‐estimation, and learning. Participants indicated their mood as 'lockdown' was eased. Performance typically improved as opportunities for social contact increased. Interactions between participant sub‐groups and timepoint demonstrated that performance was shaped by individuals' social isolation levels. Social isolation is linked to cognitive decline in the absence of ageing covariates. The impact of social isolation on cognitive function should be considered when implementing prolonged pandemic‐related restrictive conditions.